(untitled) (Fiep Bulletin - online, 2015)
A very important event for our Organization will take place this year, during a great World Congress of Physical Education, in Madrid, from the 13th to the 17 the september: it is a question of its 10th General Assembly after Brussels (1923, 1935 , 1958, 1963), Stockholm (1930, 1939, 1949, Istambul (1953), and Rome 1960).